Unlocking the power of reticulocyte analysis: Advancing care for patients with abnormal haemoglobin variants at Eastern Regional Hospital, Koforidua - Richard Vikpebah Duneeh; Israel Bedzina; Melody Yaaba Korkor Johnson; Francis Agyei Amponsah; Wina Ivy Ofori Boadu; Kenneth Ablordey (PLoS ONE, 2025)
Reticulocytes are immature erythrocytes that have been released into the peripheral circulation after being extruded from the bone marrow. However, it has not been investigated whether these reticulocyte indicators are helpful in treating conditions linked to abnormal haemoglobin variants. In the current investigation, participants with abnormal haemoglobin variants were evaluated for the utility of reticulocyte parameters using a high-end haematology analyser. We conducted a prospective cross-sectional study among 217 participants with abnormal haemoglobin variants at the Eastern Regional Hospital, Koforidua. Statistical analyses were performed with IBM SPSS V.26.0 (Chicago, IL, USA) and R programming language version 4.2.3. A p-value of < 0.05 was considered statistically significant for all analyses. We found a significant association between age groups and anaemia severity (p = 0.016). Haemoglobin levels varied significantly among abnormal haemoglobin variants (p < 0.05), with the “SF” phenotype showing the lowest levels. Production defects accounted for 1.4% of cases, while maturation defects were present in 91.7%. An increase in low-fluorescence reticulocytes was linked to a 0.03 g/dL rise in haemoglobin (β = 0.03, p < 0.05), whereas increases in high- and medium-fluorescence reticulocytes led to declines of 0.069 g/dL and 0.052 g/dL, respectively (p < 0.05). Haemoglobin levels were significantly lower in participants with maturation abnormalities (p < 0.01). The study found relationships between the severity of anaemia, age, and haemoglobin phenotypes in individuals with abnormal haemoglobin variants. Given the predominance of maturation defects, management aimed at addressing ineffective erythropoiesis is necessary. The differences in how reticulocyte subpopulations affect haemoglobin levels imply that reticulocyte indices may be helpful biomarkers for monitoring and guiding therapeutic approaches.